National health accounts of Kazakhstan - Organisation for Economic Co-operation and Development (OECD reviews of health systems, ISSN 1990-1429, 2018)
Summary.
Keywords: terveydenhuolto : Kazakstan; terveydenhuoltomenot : Kazakstan; terveydenhuolto : rahoitus : Kazakstan; kansantalouden tilinpito : Kazakstan; terveydenhuolto : tilastot : Kazakstan